Unraveling the pathogenic mechanism of a novel filamin a frameshift variant in periventricular nodular heterotopia - Xue, Chunran; Wang, Yishu; Peng, Jing; Feng, Sisi; Guan, Yangtai; Hao, Yong (Frontiers in Pharmacology, 2024)
Background: Periventricular nodular heterotopia (PVNH) is a neuronal migration disorder caused by the inability of neurons to move to the cortex. Patients with PVNH often experience epilepsy due to ectopic neuronal discharges. Most cases of PVNH are associated with variations in filamin A (FLNA), which encodes an actin-binding protein. However, the underlying pathological mechanisms remain unclear. Methods: Next-generation sequencing was performed to detect variants in patients with PVNH, and the findings were confirmed using Sanger sequencing. Iterative threading assembly refinement was used to predict the structures of the variant proteins, and the search tool for the retrieval of interacting genes/proteins database was used to determine the interactions between FLNA and motility-related proteins. An induced pluripotent stem cell (iPSC) line was generated as a disease model by reprogramming human peripheral blood mononuclear cells. The FLNA expression in iPSCs was assessed using western blot and quantitative real-time polymerase chain reaction (qRT-PCR). Immunofluorescence analysis was performed to determine the arrangement of F-actin. Results: A novel FLNA frameshift variant (NM_001456.3: c.1466delG, p. G489Afs*9) was identified in a patient with PVNH and epilepsy. Bioinformatic analysis indicated that this variation was likely to impair FLNA function. Western blot and qRT-PCR analysis of iPSCs derived from the patient's peripheral blood mononuclear cells revealed the absence of FLNA protein and mRNA. Immunofluorescence analysis suggested an irregular arrangement and disorganization of F-actin compared to that observed in healthy donors.Our findings indicate that the frameshift variant of FLNA (NM_001456.3: c.1466delG, p. G489Afs*9) impairs the arrangement and organization of F-actin, potentially influencing cell migration and causing PVNH.